Study on Dynamic Response Characteristics and Damage Mechanism of Tunnel Lining at Entrance of Shallow Bias Tunnel - Lin Li; Xiaodan Guo; Zuyin Zou; Zhanyuan Zhu; Zihong Guo; Weimin Xiao; Deping Guo (Shock and Vibration)
The structural damage of the lining structure at the entrance of a tunnel is the most common instability problem. The instability problem may cause dynamic effects such as earthquakes and blasting. Based on the seismic damage data collected from previous major earthquakes at the entrance of shallow-buried tunnel, the shaking table test and numerical simulation are used to analyze dynamic response characteristics and damage evolution characteristics of the tunnel in the shallow-buried hole at 30°. The study revealed the stress characteristics of tunnel lining and the mechanism of structural damage under earthquake excitation. The research results show that the biased tunnel (30°) is susceptible to damage on the unsymmetrical loading side, the biased ground surface leads to acceleration, and high speed also significantly increases the effect. The biased side leg of the tunnel lining cross section is a location with a large internal force distribution. The biased tunnel has a relatively unfavorable internal force value distribution and a larger peak, and the peak at the larger bias side has the largest peak value. The skewback and spandrel portion of the biased tunnel lining load are more likely to be damaged.